Optimizing patient recruitment in community pharmacies using implementation science principles: a Study Within A Trial (SWAT) - Kirstin Messner; Alexa Rosenthaler; Manuel Leuenberger; Meret Berger; Lena Walz; Isabelle Arnet; Samuel Allemann (Trials, 2026)
Abstract Background Decentralized trial approaches involving community pharmacies have gained increasing attention. However, recruitment in community pharmacies faces complex conditions and tailored strategies are necessary. Applying implementation science principles is a promising but underrepresented approach to facilitate recruitment processes. On the example of adherence-enhancing services, we aimed to investigate influencing factors to trial recruitment in the community pharmacy setting and to identify implementation strategies that can optimize trial recruitment. Methods We conducted a qualitative Study Within A Trial (SWAT) embedded within two ongoing trials evaluating adherence services provided in pharmacies. Pharmacists and patients invited to one of the host trials were asked to explain reasons for participation or non-participation in written form, at the pharmacy counter, in short telephone interviews, or in semi-structured interviews. In an inductive/deductive hybrid analysis, we coded all responses deductively based on the constructs of the updated Consolidated Framework for Implementation Research. By using the CFIR-ERIC Matching Tool, barriers were matched to strategies from the Expert Recommendations for Implementing Change. Additionally, we analyzed all data inductively. Results Thirty-one community pharmacists and 127 patients stated reasons for accepting or declining to participate in one of the studies. Nine pharmacists participated in semi-structured interviews. We identified 18 barriers and 9 facilitators related to trials in community pharmacies. Most barriers were associated with the Individuals domain of the CFIR. Factors influencing innovations’ acceptance were mainly linked to innovations’ adaptability and complexity. Policies and Laws created an additional strong barrier to recruitment. With the CFIR-ERIC Matching Tool, we identified 13 implementation strategies such as local champions, new funding, and ongoing discussions, consultations, and training of study sites. The inductive analysis revealed 8 additional strategies not identified by the CFIR-ERIC Matching Tool, concerning general study design, study materials, and the recruitment process. Conclusions Trial recruitment in community pharmacies requires targeted implementation strategies addressing local barriers and including known facilitators. Most promising strategies include implementation plans, information materials, and local pharmacy champions, which may help overcome limited resources. Although our results were obtained in adherence-enhancing services, strategies targeting barriers in the Inner Setting and Outer Setting may be particularly transferable to other pharmacy services. Trial registration ClinicalTrials.gov NCT06094062 (PIPPI-Study). Registered on 23 October 2023; and NCT06126900 (SMAPP-Study). Registered on 13 November 2023.